A facile synthesis by spark plasma sintering of mobile lithium ions into oxynitride glass-ceramic matrix: Insight and perspective - Sharafat Ali; Abbas Saeed Hakeem; Hussain Alslman; Natalia Anna Wójcik (Journal of Materials Research and Technology)
The quest for efficient energy storage solutions has led to the development of solid-state Li-on batteries (SSBs), which utilize solid-state electrolyte (SSE) materials instead of organic liquid electrolytes. This study investigates the effect of increasing Li content in a Ca11Al14Si16O49N10 glass-ceramic material on its structural, thermal, physical, and electrical properties. Spark Plasma Sintered (SPS) glass-ceramic samples with varying Li content (6–21 wt% of Li₂O) were analyzed. X-ray diffraction (XRD) analysis exhibited amorphous patterns for both the oxynitride parent glass and the same undoped glass which was sintered via SPS. Furthermore, the XRD analysis revealed changes in the crystalline phases with varying Li content, indicating a complex relationship between Li concentration and crystallinity. With increase in Li content, the crystallinity in the samples decreases. Optical and scanning electron microscopy (SEM) studies demonstrate alterations in microstructural features, notably an increase in the number of Li-rich phases. Thermal analysis reveals fluctuating thermal expansion and conductivity trends, with significant increases observed up to a certain Li content threshold. Ionic conductivity studies indicate a complex relationship between Li content, activation energy, and conduction mechanisms, with optimal conductivity observed at specific Li concentrations. These findings provide valuable insights into the design and optimization of SSE materials for next-generation energy storage applications.